Simulation of Challenging Electromagnetic Problems Using a Massively Parallel Finite Element Method Solver - Sheng Zuo; Daniel Garcia Donoro; Yu Zhang; Yang Bai; Xunwang Zhao (IEEE Access, 2019)
This communication presents an efficient massively parallel finite element method solver for the solution of complex and electrically large electromagnetic problems with arbitrary structures. The solver makes use of a domain decomposition algorithm to decompose the original problem into several non-overlapping sub-domains that may be solved independently in parallel through the application of the corresponding transmission conditions on the interfaces of the adjacent sub-domains. A numerical exact mesh truncation algorithm called finite element-iterative integral equation evaluation, accelerated with multilevel fast multipole algorithm, is implemented to meet the highly accurate requirements of today's challenging simulations. What's more, a hybrid message passing interface and an open multi-processing parallel framework are designed to achieve large-scale parallel performance on supercomputers. Through several numerical examples, the accuracy, effectiveness, and scalability of the proposed solver will be demonstrated, achieving more than 60% parallel efficiency on an eight times CPU core scale (from 1280 to 10 240 cores).